A First Season of Excavations at the Urartian Citadel of Kayalıdere (The Expedition – The Natural Environment – The Historical Setting of Kayalidere – General Description of the Site – The Gateways and the Approach Road – The Temple and its Forecourt – The Objects from the Temple Area – The Terraces of the Upper Citadel – The Pithos Room and the Pithoi – Rooms Along the Edge of the Cliff – The Plunder – Tomb A) - Burney, C. A.
The Pithos Room and the Pithoi (88-90, fig. 17: The Pictographs on the Pithoi).